Turning the Cocopith Waste into Myceliated Biocomposite to Make an Insulator - Diana Susyari Mardijanti; Erri Noviar Megantara; Ayi Bahtiar; Sunardi Sunardi (International Journal of Biomaterials)
Cocopith is the main waste of the coconut coir milling industry, which has not been handled properly until now. Burning cocopith as a response to land availability concerns for storing waste has an impact on pollution for the surrounding environment. Efforts to reduce, reuse, recycle, and remanufacture cocopith waste provide better economic value for waste. The method used in this research is one with quantitative and qualitative approaches. The AAS method is used to test the concentration of cocopith chemical elements, while lignin and cellulose levels were tested using data methods. The test results obtained that the highest chemical elements are sulfur and chlorine; the sulfur content in 1 kg of cocopith is 24,000 mg and chlorine content is 10,371 mg. Meanwhile, the other results showed that lignin levels in cocopith (22.7%) are higher than cellulose content (10.27%). The test results of cocopith characteristics from the methods mentioned above showed that the chemical content of sulfur and chlorine and lignin, more so than cellulose, causes cocopith to have the potential to insulate thermally. Based on this potential, cocopith is processed into mycelium-based biocomposite that serves as an insulator. Maximum stress and tensile stress of this biocomposite have been tested through flexural strength tests with the ASTM-D7264 method. The biocomposite feasibility of the material as an insulator was shown through a thermal conductivity test at temperatures of 13°C–40°C. This showed a thermal conductivity value of 0.0887241 ± 0.002964 W/mK. This value is in the range of 0.01–1.00 W/mK, which is a recommended value for the thermal conductivity insulator.